(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Sexual assault and indecent behaviour towards women have been occurring from before the rinderpest era to the present day. Due to the traumatic nature of these incidents and the associated social stigma, fewer than 10% of survivors of sexual assaults seek justice in court of law. Judiciary requires medical evidence along with the victim’s testimony to corroborate the incident and provide justice for those who are in need. The present study aims to acquire data regarding incidence of the physical injuries as well as genital injuries in sexually assaulted victims. This study is a retrospective review with analysis of case sheet records documented by doctors. It examines women who reported sexual assault to the Department of Obstetrics and Gynaecology (OBG) at tertiary health care center between January 2018 to December 2022. The main outcome measures are the presence of physical-injuries as well as injuries over genitalia. A total of 222 victims of sexual assault were included. Out of these 222 cases, 122 victims suffered from only physical injuries, 62 victims suffered from both physical injuries as well as genital injuries, and 38 victims did not have any kind of injuries. This study shows that approximately 54.9% of the victims examined by doctors exhibited evidence of only physical injuries, 27.9% exhibited evidence of genital injuries, and 17.1% did not show any injuries. It is important to remember that the absence of injuries (physical injuries and genital injuries) does not exclude the possibility of rape.